A= 2018-2017 /2018+2017 và B =2018^2 -2017^2 / 2018^2 +2017^2

By Audrey

A= 2018-2017 /2018+2017 và B =2018^2 -2017^2 / 2018^2 +2017^2

0 bình luận về “A= 2018-2017 /2018+2017 và B =2018^2 -2017^2 / 2018^2 +2017^2”

  1. Ta có:

    `A=(2018-2017)/(2018+2017)=1/(2017+2018)`

    `B=(2018^2-2017^2)/(2017^2+2018^2)`

    `=[(2018-2017)(2018+2017)]/(2017^2+2018^2)`

    `=(2017+2018)/(2017^2+2018^2)`

    Hiển nhiên: `(2017+2018)^2>2017^2+2018^2`

    `⇒2017+2018>(2017^2+2018^2)/(2017+2018)`

    `⇒1/(2017+2018)<(2017+2018)/(2017^2+2018^2)`

    Hay `A<B`

     

    Trả lời

Viết một bình luận